> 数学 >
(1) (5a的平方-ab+1)-(-4a的平方+2ab+1) (2) 3(2x的平方y-xy的平方)-(4a的平方+3x的平方+3x的平方y)
其中x=-1 y=2 (3) m-{n-2m+[3m-(6m+3n)-5n]} 其中m=-1 y=2
(2) 3(2x的平方y-xy的平方)-(4xy的平方+3x的平方+3x的平方y)
人气:322 ℃ 时间:2020-04-10 14:01:05
解答
(1) (5a的平方-ab+1)-(-4a的平方+2ab+1)= 5a^2-ab+1+4a^2-2ab-1= 9a^2-3ab(2) 3(2x的平方y-xy的平方)-(4a的平方+3x的平方+3x的平方y)= 6x^2y-3xy^2-4a^2-3x^2-3x^2y= 3x^2y-3xy^2-4a^2-3x^2其中x=-1 y=2则上式=3...第二题写错了是3(2x的平方y-xy的平方)-(4xy的平方+3x的平方+3x的平方y)3(2x的平方y-xy的平方)-(4xy的平方+3x的平方+3x的平方y)= 6x^2y-3xy^2-4xy^2-3x^2-3x^2y= 3x^2y-3xy^2-4xy^2-3x^2= 3x^2y-7xy^2-3x^2其中x=-1 y=2则上式=3*(-1)^2*2-7*(-1)*2^2-3*(-1)^2 =6+28-3 =31
推荐
猜你喜欢
© 2024 79432.Com All Rights Reserved.
电脑版|手机版